Filial Therapy to Improve Emotional Regulation in Child with Temper Tantrums - Rezki, Muhammad; Zulfiana, Uun (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2025)
Tantrums are a common emotional response in children, often occurring when they struggle to regulate their emotions. This study focused on the use of filial therapy in improving emotional regulation and reducing tantrum frequency in a 9-year-old boy. Filial therapy was chosen for its emphasis on parental involvement, strengthening the parent-child bond, and teaching emotional regulation skills. The study was a single subject research design, that began with an initial assessment through interviews, observations, and psychological tests. This was followed by an 11-session filial therapy. The results showed a significant improvement in the participant’s emotional regulation, leading to a reduction in tantrum behavior. The ERQ scores during the pretest were 25 (moderate category), increasing to 47 (high category) in the post-test, and further rising to 55 (high category) in the follow-up assessment. These findings highlight the essential role of parents in supporting their child's emotional development and the use of filial therapy to improve parent-child dynamics and reduce tantrums.